Comparing the effect of aerobic exercises and guided imagery on depression in patients with multiple sclerosis - Abd-ElRaheem , Hoda Z.; Elwishy , Abeer A.; Shehata , Hatem Samir M.; Awad , Amina (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
Background: Depression is commonly found in multiple sclerosis (MS), yet, it still undertreated. Objective: To compare the effect of aerobic exercise and Heal Light Guided Imagery (HLGI) on depression in patients with Relapsing-Remitting MS (RRMS) at short-term and one month follow up. Methods: A parallel group trial was conducted for eight successive weeks on 45 patients with RRMS, aged between 20 to 40 years old, and randomly assigned into three groups; 15 patients each. Aerobic exercise (AE) group received 30 minutes of stationary bicycle twice weekly, HLGI group received one session (60 minutes) weekly, and a wait-list control group. The Beck Depression Inventory (BDI), Fatigue Severity Scale (FSS) and Paced Auditory Serial Addition Test (PASAT), were measured pre-treatment, post-treatment and one month follow up. Results: The BDI showed significant reduction in AE and HLGI post-treatment and at follow up, with no statistical difference between the two groups. Compared with control group, the BDI was significantly reduced in intervention groups post-treatment and at follow up, while the FSS showed significant reduction in intervention groups only post-treatment. The PASAT showed significant increase post-treatment and at follow up in all groups, with no significant difference between them. Conclusion: Aerobic exercise and HLGI can similarly reduce depression in people with RRMS.